Effect of Batter Ageing on Microbial, Physiochemical Changes and Sensory Quality of Sel-roti - Dahal, Santosh; Katawal, Surendra Bahadur (Journal of Food Science and Technology Nepal, 2014)
Sel-roti is a deep-fat fried, puffed, circular spongy doughnut like indigenous,non- alcoholic fermented cereal product of Nepal. A study was conducted to study the effect of batter ageing on physiochemical and microbial changes and its impact on sensory quality of Sel-roti.Ten samples of batters were aged for 9 h at 3 h interval at temperatures30°C, 40°C and 50°C.After ageing, acidity as lactic acid, reducing sugar and total sugar contents of the batter had increased significantly (P<0.05). The total sugar content of the batter started to decrease after 6 h of ageing. During the ageing period of 3 hour bulk density of products were decreased significantly (p<0.05) for all temperatures of ageing but after 3 hours of ageing it was increased slightly for 40°C. Fat uptake of sel-rotifound to decrease as ageing proceeds. Lactic acid bacteria, yeasts and mold co-existed in sel-rotibatter. LAB and yeast count at the end of 9 hour of aging was higher at 30°C than at 40°C. LAB and yeast count at 50°C was markedly decreased during 9 hour of ageing of batter. Mold count in the samples of batter during aging was decreased at all temperatures. Among study time and temperature of ageing quality of sel-roti prepared from batter aged at 30°C for 6 hour was found to be good in terms of sensory quality and cost effectiveness. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11721 J. Food Sci. Technol. Nepal, Vol. 8 (12-17), 2013